Determinants of Dyadic Relationship and Its Psychosocial Impact in Patients with Parkinson’s Disease and Their Spouses - Michaela Karlstedt; Seyed-Mohammad Fereshtehnejad; Dag Aarsland; Johan Lökk (Parkinson's Disease)
The caregiver-care receiver relationship (mutuality) in Parkinson’s disease (PD) and its association with motor and non-motors symptoms, health-related quality of life (HRQoL), and caregiver burden have not fully been investigated. The aim of our study was to explore if (1) the level of mutuality perceived by PD-patients and PD-partners differs, (2) different factors are associated with perceived mutuality by PD-patients and PD-partners, and (3) mutuality is associated with PD-patients health-related quality of life (HRQoL) and caregiver burden. We collected data on motor signs (UPDRS III), non-motor manifestations (NMSQuest), PD-patients’ cognition (IQCODE), mutuality scale (MS), PD-patients’ HRQoL (PDQ8), and caregiver burden (CB) from 51 PD dyads. Predictors were identified using multivariate regression analyses. Overall, the dyads rated their own mutuality as high with no significant difference between the dyads except for the dimension of reciprocity. PD-patients’ MS score (p=.001) and NMSQuest (p ≤ .001) were significant predictors of PDQ8. Strongest predictor of CB was PD-partners’ MS score (<.001) and IQCODE (p=.050). In general, it seems that non-motor symptoms contribute to a larger extent to the mutual relationship in PD-affected dyads than motor disabilities.